A Photoresponsive Orthogonal Supramolecular Complex Based on Host–Guest Interactions. Issue 11 (27th January 2017) - Wang, Dongsheng; Wagner, Manfred; Saydjari, Andrew K.; Mueller, Julius; Winzen, Svenja; Butt, Hans‐Jürgen; Wu, Si
Abstract: We synthesized a novel green‐light‐responsive tetra‐ ortho ‐isopropoxy‐substituted azobenzene (ipAzo). Cis ‐ipAzo forms a strong host–guest complex with γ‐cyclo dextrin (γ‐CD) whereas trans ‐ipAzo binds weakly. This new photoresponsive host–guest interaction is reverse to the well‐known azobenzene (Azo)/α‐cyclodextrin (α‐CD) complex, which is strong only between trans ‐Azo and α‐CD. By combining the UV‐light‐responsive Azo/α‐CD and green‐light‐responsive ipAzo/γ‐CD host–guest complexes, a photoresponsive orthogonal supramolecular system is developed. Abstract : Working together : A photoresponsive orthogonal supramolecular system is developed by combining the UV‐light‐responsive Azo/α‐CD and green‐light‐ responsive ipAzo/γ‐CD host–guest complexes (see figure).